2006
DOI: 10.1093/rheumatology/kel164
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic indicators for non-recovery of non-traumatic complaints at arm, neck and shoulder in general practice—6 months follow-up

Abstract: Besides questions on complaint characteristics, information on somatization and support can help a general practitioner to recognize patients at risk of persistent complaints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 22 publications
0
42
0
3
Order By: Relevance
“…Feleus et al (4) reported an annual incidence rate of 1.1 per 100 patients in general practice in Holland and Silverstein et al (5) reported an annual incidence rate for claims of 0.1 per 100 full-time workers in the Washington state. In France, Roquelaure et al (7) reported an annual incidence rate of 2.1 per 100 workers in a shoe factory and Leclerc et al (9) reported an annual incidence rate of 4.0 per 100 workers highly exposed to physical constraints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Feleus et al (4) reported an annual incidence rate of 1.1 per 100 patients in general practice in Holland and Silverstein et al (5) reported an annual incidence rate for claims of 0.1 per 100 full-time workers in the Washington state. In France, Roquelaure et al (7) reported an annual incidence rate of 2.1 per 100 workers in a shoe factory and Leclerc et al (9) reported an annual incidence rate of 4.0 per 100 workers highly exposed to physical constraints.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of lateral epicondylitis has been estimated in general practice (3,4), on the basis of compensation claims (5), hospitals (6), and certain specific activity sectors (7)(8)(9). The estimated incidence of lateral epicondylitis ranges from 0.3-1.1 per 100 patient-years in general practice to 2.0-11.3 per 100 worker-years in specific activity sectors.…”
mentioning
confidence: 99%
“…For example, elevated scores on the Tampa Scale of Kinesiophobia or the Fear-Avoidance Beliefs Questionnaire have been associated with a longer recovery, chronic symptoms, and work loss in patients with shoulder pain. 42,59,79 Accordingly, identifying cognitive behavioral tendencies during the patient's evaluation can direct the therapist to employ specific patient education strategies to optimize patient outcomes to physical therapy interventions and potentially provide indications for referring the patient for consultation with another medical or mental health practitioner. 10 …”
Section: Componentmentioning
confidence: 99%
“…In our earlier study in this population, indicators of poor prognosis were long duration of the complaints at baseline, having musculoskeletal comorbidity, recurrent complaint, low social support, and a high somatization level. 11 Although GP characteristics, such as sex, years of experience, and type of practice, are also reported to infl uence management decisions, 12,13 in a well-organized health care system, their infl uence would be expected to be marginal and that the diagnosis, patient, and complaint characteristics would show the strongest associations with management. Furthermore, highly variable treatment that cannot be explained by differences in diagnoses and patient or complaint characteristics could indicate the need for treatment guidelines to ensure that management decisions at least can be based on available knowledge on preferable outcomes or, when not available, on costs.…”
Section: Introductionmentioning
confidence: 99%